LEGAL PROTECTION FOR CONSUMERS IN DIGITAL TRANSACTIONS IN INDONESIA - Zulkifli; Sofyan Jafar; Teuku Yudi Afrizal; Muhibuddin; Nasrianti (PT. Radja Intercontinental Publishing, 2024)
The rapid development of information technology has accelerated the growth of digital commerce (e-commerce) in Indonesia. Along with the increasing use of electronic transaction systems, various legal problems have emerged that potentially harm consumers, including online fraud, product discrepancies, delays in delivery, misuse of personal data, and the inclusion of unfair standard clauses by business actors. These conditions indicate that consumers remain in a vulnerable position within digital transactions. This study aims to analyze the effectiveness of legal protection for consumers in digital commerce transactions in Indonesia and to identify the obstacles affecting its implementation. The research employs a normative legal research method using statutory and conceptual approaches. The study examines Law No. 8 of 1999 concerning Consumer Protection, Law No. 11 of 2008 concerning Electronic Information and Transactions and its amendments, as well as Law No. 27 of 2022 concerning Personal Data Protection. The results of the study show that consumer protection regulations in Indonesia have provided a normative legal framework for safeguarding consumer rights in digital transactions. However, their implementation has not yet been fully effective due to weak supervision of digital business actors, low public legal literacy, ineffective dispute resolution mechanisms, and technological developments that progress faster than existing legal regulations. In addition, the protection of consumers’ personal data remains vulnerable due to the increasing volume of electronic data processing in e-commerce activities. This study highlights the urgency of strengthening regulatory supervision, improving digital legal literacy among the public, and optimizing personal data protection mechanisms to ensure legal certainty, justice, and security for consumers in Indonesia’s digital commerce ecosystem.